Teachers’ perspectives on code-switching and code-mixing in classroom interaction - Fathur Rizki Asani; Saidah (Balai Diklat Keagamaan Ambon, 2025)
This research is a qualitative descriptive study that explores EFL teachers' perspectives on the implementation of code-switching and code-mixing in classroom settings. Implementing observation and stimulated recall interviews using an observation sheet and video, four EFL teachers at MAN Ambon, selected through purposive sampling, were first observed and then interviewed to elaborate on their insights into the use of these linguistic strategies in teaching. Moreover, the analysis of the interactive data followed three stages: data reduction, data display, and conclusion drawing or verification. The findings reveal that teachers' perceptions are diverse, which can be divided into two main categories: positive and negative. On the positive side, teachers notice that code-switching and code-mixing are tools that enhance students' understanding, increase motivation, and aid in vocabulary acquisition. On the other hand, negative perceptions include concerns about the risk of monotonous repetition leading to students' lack of interest and the possibility of deviating from standard language norms. These findings are expected to contribute to teachers and other researchers by enriching their understanding of the pedagogical implications of language alternation practices in EFL classrooms.